UPAYA MENINGKATKAN PRODUKTIVITAS MELALUI INOVASI KEMASAN PADA USAHA KERUPUK KULIT SAPI “AYANG” DI MATARAM - Oktiani, Asri; Faezal, Faezal; Maryanti, Sri (Devote: Jurnal Pengabdian Masyarakat Global, 2024)
This community service program aims to enhance the productivity of the "Ayang" cowhide cracker business in Mataram through packaging and product innovation. The program is motivated by the challenges faced by the partner, who struggles with limited packaging capabilities, hindering the growth of product sales. The activities carried out include counseling and mentoring sessions to guide the partner in selecting and packaging products effectively, as well as conducting market research to gather consumer feedback on the new packaging. As a result of these efforts, the partner experienced a shift in mindset regarding the importance of packaging innovation and gained insight into effective packaging options, prompting a willingness to improve packaging to boost sales productivity. It is hoped that this initiative will motivate the partner to continue innovating, learning, and exploring new knowledge related to other marketing strategies, such as product promotion and distribution.